2018
DOI: 10.1007/s00380-018-1137-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and peripartum outcomes in pregnant women with cardiac disease: a nationwide retrospective cohort study in Japan

Abstract: Although the number of pregnancies in women with cardiac disease is increasing worldwide, there are few data concerning their clinical characteristics and peripartum outcomes. Using the Diagnosis Procedure Combination database between 2008 and 2014 in Japan, we retrospectively identified pregnant women who underwent high-risk delivery due to obstetric or non-obstetric comorbidities. We classified eligible women into those with pre-existing cardiac disease (cardiac disease group) and those with non-cardiac como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…During the study period, no deaths associated with childbirth were observed. This was consistent with previous reports from Japan [13][14][15]. On the other hand, the incidence of peripartum cardiovascular events, most of which were heart failure, arrhythmias, and thromboembolic events, were discordant between the studies [5,[13][14][15].…”
Section: Peripartum Adverse Cardiovascular Events and Readmissions Within 1 Yearsupporting
confidence: 91%
See 4 more Smart Citations
“…During the study period, no deaths associated with childbirth were observed. This was consistent with previous reports from Japan [13][14][15]. On the other hand, the incidence of peripartum cardiovascular events, most of which were heart failure, arrhythmias, and thromboembolic events, were discordant between the studies [5,[13][14][15].…”
Section: Peripartum Adverse Cardiovascular Events and Readmissions Within 1 Yearsupporting
confidence: 91%
“…This was consistent with previous reports from Japan [13][14][15]. On the other hand, the incidence of peripartum cardiovascular events, most of which were heart failure, arrhythmias, and thromboembolic events, were discordant between the studies [5,[13][14][15]. The discordance may potentially be attributed to the definition or severity of adverse events.…”
Section: Peripartum Adverse Cardiovascular Events and Readmissions Within 1 Yearsupporting
confidence: 90%
See 3 more Smart Citations